Volume 2, Parts a and B 2004
DOI: 10.1115/ht-fed2004-56435
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Investigation of Unsteady and Acoustic Characteristics of Counter-Rotating Fans

Abstract: The matter of developing counter-rotating fans for advanced next generation aeroengines with ducted and unducted propfans is very important [1]. Counter-rotating fans can be made with fixed blades. This article considers tractor propfans consisting of two counter-rotating rotors of variable pitch (VPR) which valuable property is the possibility to turn their blades about the radial axis in order they can take the optimal position in direct thrust regimes, and to obtain a reverse thrust when turning them by a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The other challenge is to significantly reduce noise levels (both, cabin and far fields) to a level at least being comparable with current turbofan technologies. Progress has been made in both fields (aerodynamics and acoustics) by applying modern design methodologies, starting from three-dimensional (3D) Euler simulations [1] to the application of highly sophisticated 3D unsteady Reynolds-averaged Navier-Stokes (URANS) flow solvers coupled with far field predictions methods [4][5][6]. A methodology using a 3D inverse method for open rotor aerodynamic and acoustic optimization has been applied successfully showing great potential in order to reach the aforementioned objectives [7].…”
Section: Introductionmentioning
confidence: 99%
“…The other challenge is to significantly reduce noise levels (both, cabin and far fields) to a level at least being comparable with current turbofan technologies. Progress has been made in both fields (aerodynamics and acoustics) by applying modern design methodologies, starting from three-dimensional (3D) Euler simulations [1] to the application of highly sophisticated 3D unsteady Reynolds-averaged Navier-Stokes (URANS) flow solvers coupled with far field predictions methods [4][5][6]. A methodology using a 3D inverse method for open rotor aerodynamic and acoustic optimization has been applied successfully showing great potential in order to reach the aforementioned objectives [7].…”
Section: Introductionmentioning
confidence: 99%
“…Among the parameters affecting flow interactions is the inter-distance, which is a key-factor in reducing the noise (Holste and Neisser 1997). In this context, Brailko et al (2004) developed a numerical approach to predict the noise produced by two counter-rotating rotors of the SV-27 propfan separated by an inter-distance of 650 and 950 mm, and have concluded that the emitted noise and the acoustic pressure spectra are with good agreement with the experimental results. This paper contributes to the study of the rotor-rotor flow interactions in a configuration of CRF, and their consequences on the aerodynamic loading of FR and RR and the overall performance of CRF.…”
Section: Introductionmentioning
confidence: 94%
“…When the required pressure developing capability exceeds that of a single fan by a factor of between two and two and a half, a common practice within the industrial fan community is to configure two fans, counterrotating in series [68]. The use of two counterrotating fans is common in tunnel ventilation systems, and engineers occasionally have adopted it in wind tunnel applications.…”
Section: Rotor-stator Interaction and Contrarotating Fansmentioning
confidence: 99%
“…The primary advantage of the frozen rotor approach is that the rotor to rotor or rotor to stator coupling does not require a moving mesh. The relative position of the two rows is fixed in time, with relative motion managed using different frames of reference and adding Coriolis and centrifugal forces to the momentum equation in the rotating frame of [68]. In contrast to the mixing plane approach, the frozen rotor approach is able to account for a nonuniform circumferential distribution of velocity and pressure.…”
Section: Rotor-stator Interaction and Contrarotating Fansmentioning
confidence: 99%